Rekonstruksi Pasal 66 Ayat (3) Undang-Undang No. 29 Tahun 2004 Tentang Undang-Undang Praktik Kedokteran Terkait Tata Cara Pengaduan Tindakan Malapraktik Dokter di Indonesia - Baby Ivonne Susan Kainde; Ika Dewi Sartika Saimima; Yurnal (Jurnal Hukum Sasana, 2021)
The confusion in how to report doctors' malpractice actions regulated by Article 66 of the Medical Practice Law is triggered by paragraph 3 of Article 66 of the Medical Practice Law (UUPK). This paragraph provides an opening for the multi-interpretation way to report suspicions of doctor's malpractice. Even though it is clear that in paragraph 1 article 66 (UUPK) that a violation of the interest of the right is a civil violation and it does not necessarily mean that there is an element of crime and the Honorary Council of Indonesian Medical Discipline (MKDKI) is appointed as the first line of reporting. MKDKI will judge the case as deliberate and serious negligence (Criminal element) or a Medical Risk. But the facts in the mandate of the law are not implemented because many cases of doctor malpractice are immediately brought to the legal channels (police and courts) and this happens because they are accommodated in paragraph 3 of article 66 of the UUPK. Conflict between legal norms of this research is in paragraphs 1 and 3 of article 66 of the UUPK. Multiple interpretations of reporting methods for the medical profession suspected of committing malpractice The medical profession is very vulnerable to multiple charges and there is no legal protection for doctors. Therefore this paper is to see how the correct procedure for complaints of doctor malpractice cases according to the Law on Medical Practice. The research method is juridical normative, namely research conducted by examining primary, secondary and tertiary legal materials. The alternative solution offered in this research is in the form of reconstruction (rearranging) paragraph 3 of article 66 of the Medical Practice Law.